Comparison of Hospital Stay between On Table Extubation Versus ICU Extubation in Off-Pump CABG - Tariq, Zamain; Mahmood, Gul E Zaahra; Amjad, Ahsan; Tahseen, Tavyamn; Gul, Samreen; Ul Hassan, Syed Imran (Journal of Neonatal Surgery, 2025)
Background: Early extubation following off-pump coronary artery bypass grafting (CABG) has been suggested to reduce complications and shorten hospital stay. However, the safety and efficacy of on-table extubation compared to intensive care unit (ICU) extubation remain debated. Objectives: To compare early outcomes between on-table extubation and ICU extubation in patients undergoing off-pump CABG. Study Design & Setting: A study conducted at Department of Anesthesia, Punjab Institute of Cardiology, Lahore from 27 May 2025 to 27 September 2025 Methodology: A total of 248 patients undergoing elective off-pump CABG were included and divided into two groups: Group A (n = 124) underwent on-table extubation, while Group B (n = 124) underwent ICU extubation. Baseline characteristics, intraoperative variables, and postoperative outcomes were recorded. Stratification was performed for age, gender, diabetes mellitus, hypertension, and hospital stay to control for confounders. Data were analyzed using SPSS version 25.0, with p ≤ 0.05 considered statistically significant. Results: Both groups were comparable in terms of baseline demographics, risk factors, and intraoperative parameters (p > 0.05). The mean ICU stay was significantly shorter in Group A (1.4 ± 0.6 days) compared to Group B (2.6 ± 0.9 days, p < 0.001). Hospital stay was also reduced in Group A (5.8 ± 1.4 days vs. 7.1 ± 1.6 days, p = 0.061), with a higher proportion discharged within 7 days (76.6% vs. 62.9%, p = 0.021). Stratification analysis showed consistently shorter hospital stays across subgroups of age, gender, diabetes, and hypertension in Group A. Conclusion: On-table extubation after off-pump CABG is a safe and effective strategy associated with shorter ICU and hospital stays without increasing perioperative risks